2023
DOI: 10.1007/jhep04(2023)043
|View full text |Cite
|
Sign up to set email alerts
|

Tachyonic production of dark relics: a non-perturbative quantum study

Abstract: We study production of dark relics during reheating after the end of inflation in a system consisting of a non-minimally coupled spectator scalar field and the inflaton. We derive a set of renormalized quantum transport equations for the one-point function and the two-point function of the spectator field and solve them numerically. We find that our system can embody both tachyonic and parametric instabilities. The former is an expected result due to the non-minimal coupling, but the latter displays new featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Although this particular model, in its simplest version, is ruled out by CMB observations, it allows us to compare our results with previous literature (see e.g. [15,16,19,21,22]), and, furthermore, our analysis can be carried out in the same way for more realistic potentials. The dynamics for the inflaton is analytically solved at the onset of inflation, while the transition to the reheating epoch is modeled numerically.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although this particular model, in its simplest version, is ruled out by CMB observations, it allows us to compare our results with previous literature (see e.g. [15,16,19,21,22]), and, furthermore, our analysis can be carried out in the same way for more realistic potentials. The dynamics for the inflaton is analytically solved at the onset of inflation, while the transition to the reheating epoch is modeled numerically.…”
Section: Introductionmentioning
confidence: 82%
“…The theory of quantum fields in curved spacetimes accommodates a plethora of unexpected phenomena such as Hawking radiation [1], the Unruh effect [2], or entanglement across horizons [3][4][5][6], that have changed our perspective on the interplay between quantum fields and gravity. Gravitational particle production due to the spacetime dynamics [7,8] is one of these phenomena and can be particularly important during the early stages of the universe, since it may be able to explain the dark matter abundance, as it has been extensively discussed in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The rapidly evolving spacetime during inflation [24][25][26] and the consequent transient to reheating [27][28][29][30][31] can produce a significant density of particles for any field non-conformally coupled to the geometry, regardless of its interaction with other fields.…”
Section: Introductionmentioning
confidence: 99%
“…These ideas have been applied mainly to scalar fields [16][17][18][19][20][21][22][23][24], but also to vectors and fermions in the references [25][26][27][28][29]. Moreover, recent works have shown that if one wants to consider gravitational production to obtain robust constraints on the parameters of the field, a detailed characterization of spacetime dynamics is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The true particle-antiparticle mixing on the other hand, is relevant e.g. for particle production in the early universe during the (p)reheating phase after inflation [56,57].…”
Section: Introductionmentioning
confidence: 99%